-92=4(3k-2)

Simple and best practice solution for -92=4(3k-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -92=4(3k-2) equation:


Simplifying
-92 = 4(3k + -2)

Reorder the terms:
-92 = 4(-2 + 3k)
-92 = (-2 * 4 + 3k * 4)
-92 = (-8 + 12k)

Solving
-92 = -8 + 12k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-12k' to each side of the equation.
-92 + -12k = -8 + 12k + -12k

Combine like terms: 12k + -12k = 0
-92 + -12k = -8 + 0
-92 + -12k = -8

Add '92' to each side of the equation.
-92 + 92 + -12k = -8 + 92

Combine like terms: -92 + 92 = 0
0 + -12k = -8 + 92
-12k = -8 + 92

Combine like terms: -8 + 92 = 84
-12k = 84

Divide each side by '-12'.
k = -7

Simplifying
k = -7

See similar equations:

| 8x^2+2x+-15=0 | | z+.625=.9375 | | (x+5)2=108 | | (7+y)(4y+5)=0 | | 20+12x=-128 | | (m^5n^5)^1/6/3(mn)^-1/6 | | 3n=1/81 | | 224=d-12 | | (33*5280)/(60) | | 70=al | | 6r+9=16+7r | | 9x^2-11x-2=0 | | x-5=1/12 | | (16y^3/8y^4)^-4 | | 12+6x=5x+6 | | 2(3x-4)=118 | | (4-1/2c)-1/3[3/4(1-2c)]1/12c | | 2x+5=-4x-6 | | (64m^1/2n÷m^-2n4/3)^1/2 | | 203/x=7 | | x/21=21 | | 4x+6=-2x-6 | | 14y^2-12y+3=0 | | e^2x=-4x | | .30x+6y=200 | | 3.5y-2.5y-6.3=-1.0-2.5 | | 2x+3-8(x+1)=3x+2 | | 5q+6=20 | | -3r+10=15r+3g | | x+37=88 | | e^2=-4x | | (3y+23)=9y-11 |

Equations solver categories